Finalité Revisited: On the Dynamics of Supranational Integratedness - Graser, Alexander (Federalism as the Future of the Diverse EU?, 2025)
Interpreting European supranationality as a long-standing, highly institutionalised practice of multilevel liberal communitarianism, the present contribution reflects on the current situation and future prospects of the EU. Its tentative diagnosis is that there may no longer be any clear directionality, while a sustained dynamism persists. The contribution hence calls for a terminological de-rigidification to better grasp the current set-up, and it proposes the concept of institutional fluidity as a potential desideratum for a new constitutional balance.Keywords: European integration, finalité, liberal communitarianism, terminological de-rigidification, institutional fluidity.